2008
DOI: 10.1038/sj.mt.6300374
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Migration of Mesenchymal Stem Cells Modified With CXCR4 Gene to Infarcted Myocardium Improves Cardiac Performance

Abstract: With the goal of devising a non-invasive cell therapy for cardiac repair that may be well tolerated by patients with myocardial infarction (MI), this study evaluated the efficacy of intravenous infusion of genetically modified mesenchymal stem cells (MSCs) overexpressing CXC chemokine receptor 4 (CXCR4). CXCR4 is the cognate receptor for stromal-derived factor-1 (SDF-1), a chemokine required for homing of progenitor cells to ischemic tissues. In this study, retrovirally transduced MSCs constitutively expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
276
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 397 publications
(290 citation statements)
references
References 46 publications
11
276
1
2
Order By: Relevance
“…The SDF-1/CXCR4 axis has been implicated in the migration of MSCs to the impaired brain after hypoglossal Pre-treatment with IL-1b enhances the efficacy of MSC transplantation HY Fan et al 479 nerve injury in a rat model, resulting in tissue regeneration, 30 and over expression of CXCR4 improves MSC migration to infracted myocardium and ameliorates cardiac performance. 31 Our results showed that IL-1b-primed MSCs significantly increased expression of CXCR4 at both the mRNA and protein levels in vitro. Altogether, these results suggest that IL-1b could enhance the ability of MSCs to target and localize to inflammatory sites and elevate their migration ability through increasing CXCR4 expression, all of which could render MSCs more efficacious in cell-based repair therapy.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The SDF-1/CXCR4 axis has been implicated in the migration of MSCs to the impaired brain after hypoglossal Pre-treatment with IL-1b enhances the efficacy of MSC transplantation HY Fan et al 479 nerve injury in a rat model, resulting in tissue regeneration, 30 and over expression of CXCR4 improves MSC migration to infracted myocardium and ameliorates cardiac performance. 31 Our results showed that IL-1b-primed MSCs significantly increased expression of CXCR4 at both the mRNA and protein levels in vitro. Altogether, these results suggest that IL-1b could enhance the ability of MSCs to target and localize to inflammatory sites and elevate their migration ability through increasing CXCR4 expression, all of which could render MSCs more efficacious in cell-based repair therapy.…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies suggest that these soluble factors, including PGE2, IL-6 and IL-8, are critical for the immunomodulatory function of MSCs. COX-2 (a key enzyme in the synthesis of PGE2), 31 IL-8 32 and IL-6 33 are known to be downstream transcripts of the IL-1b signaling pathway, but it is unclear whether this phenomenon is also the case for MSCs. We found that IL-1b could significantly elevate COX-2, IL-6 and IL-8 mRNA expression and COX-2 protein expression, while IL-1R1 siRNA-transfected MSCs showed abrogated IL-1b signaling effects ( Figure 4).…”
Section: Il-1b-primed Mscs Alters the Balance Of Immune Cellsmentioning
confidence: 99%
“…Stem cell therapy has recently been proposed as a promising strategy for cardiac repair after myocardial infarction (Mangi et al, 2003;Amado et al, 2005;Dai et al, 2005;Li et al, 2007;Xie et al, 2007;Cheng et al, 2008c;Fazel et al, 2008;Fischer et al, 2009). However, most ransplanted stem cells undergo apoptosis in the harsh microenvironment with poor blood and oxygen supply in the infarct zone (Haider and Ashraf, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results showed that increased surface CXCR4 expression was associated with enhanced MSC migration (Cheng et al, 2008a(Cheng et al, , 2008c. To determine whether SDF-1 enhanced MSC migration through modulation of cell surface CXCR4 expression, MSCs were incubated with SDF-1 before hypoxia/re-oxygenation for 16 h. Flow cytometry analysis showed that SDF-1 tended to increase surface CXCR4 expression compared to non-treated cells, but this did not reach statistical significance ( SDF-1 promotes the secretion of bFGF and VEGF through the SDF-1/CXCR4 axis Paracrine secretion of basic fibroblast growth factors (bFGF) and vascular endothelial growth factor (VEGF) is crucial for protecting MSCs in ischemic tissues (Kinnaird et al, 2004a).…”
Section: Effects Of Sdf-1 Pretreatment On Msc Surface Cxcr4 Expressionmentioning
confidence: 99%
See 1 more Smart Citation